Mortality of a captive axis deer (Axis axis) and a llama (Lama glama) due to ingestion of Wedelia glauca - Giannitti, Federico (2012)
The current study describes a naturally occurring cluster of cases of Wedelia glauca intoxication. Seven of 14 axis deer (Axis axis) and 1 of 8 llamas (Lama glama) in a zoo of Buenos Aires province, Argentina, died suddenly after ingestion of a new batch of alfalfa (Medicago sativa) hay bales contaminated with the hepatotoxic plant W. glauca. Necropsies of 1 deer and 1 llama were performed. Pathological findings in both animals included severe diffuse acute centrilobular hepatocellular necrosis and hemorrhage, and clear yellowish translucent gelatinous edema on the wall of the gall bladder and the serosa of the choledochoduodenal junction. Fragments of W. glauca plants were identified in the hay based on the botanical characteristics of the leaves. Samples of gastric contents were examined by microhistological analysis, which identified epidermal fragments of W. glauca based on the presence of characteristic uniseriate glandular hairs (trichomes), confirming recent ingestion of W. glauca in both cases. The fragments were quantified and represented 5% of all examined vegetal fragments in the deer and 10% in the llama.